Method for evaluating wettability of solid surfaces

The method of measuring the wetting height between opposed solids immersed in a liquid provides a high-accuracy, quantitative evaluation of wettability, addressing challenges with existing methods, particularly for high-temperature molten metals.

JP7666643B2Active Publication Date: 2025-04-22JFE STEEL CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023567992
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-09-06
Filing Date
2023-09-04
Publication Date
2025-04-22
Estimated Expiration
2043-09-04

AI Technical Summary

Technical Problem

Existing methods for evaluating the wettability of solid surfaces to liquids face challenges such as subjective accuracy, complex operations, and difficulty in measuring high-temperature and oxidizing melts, particularly for molten metal plating.

Method used

A method involving a pair of solids with evaluation surfaces opposed at a certain distance, immersed horizontally in the evaluation liquid, where the wetting height (difference between the liquid level penetrating into the gap and the evaluation liquid level) is measured to evaluate the surface wetting property of the solid.

Benefits of technology

This method allows for high-accuracy, quantitative evaluation of wettability without requiring load measuring equipment, suitable for high-temperature liquids like molten metal, and enables evaluation under controlled atmospheric conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666643000002
    Figure 0007666643000002
  • Figure 0007666643000003
    Figure 0007666643000003
  • Figure 0007666643000004
    Figure 0007666643000004
Patent Text Reader

Abstract

Provided is a method that makes it possible to more easily and quantitatively obtain the surface wettability of a solid with respect to a discretionary liquid. The present invention is a method for evaluating the wettability of solid surfaces in which surfaces to be evaluated in two solids are made to face each other with a space therebetween, at least all of the bottom edge sections of the two solids are arranged so as to be present on the same plane and the result is used as a test material, an immersion test is performed in which the test material is immersed in an evaluation liquid so that all of the bottom edge section of the test material is parallel to the surface of the evaluation liquid, a wetting height which is the difference between the height of the surface of the evaluation liquid and the height of the liquid surface of the evaluation liquid entering into a gap between the two solids is measured at a discretionary immersion time, and the measured value is designated as a wettability evaluation value for the solid surfaces with respect to the evaluation liquid.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention provides a method for evaluating the wettability of a solid surface, which enables the wettability of a solid surface to be evaluated simply and quantitatively with respect to various liquids under any liquid surface atmosphere. [Background technology]

[0002] In general, the wettability of a liquid and a solid is evaluated by the contact angle. This contact angle refers to the angle on the side including the liquid among the angles between a tangent drawn to the liquid and the solid surface at the contact point of the three phases of solid, liquid, and gas. The contact angle between a liquid and a solid is usually measured by the sessile drop method, as shown in, for example, Non-Patent Document 1. This method includes a method of directly measuring the contact angle and a method of photographing the outline of a droplet and measuring the angle by image analysis. In fact, Non-Patent Document 3 describes the sessile drop method, drop A method for evaluating the static wettability of molten Zn-Al solution on various oxides by the method has been described.

[0003] Another wettability evaluation method is the meniscograph method. In the meniscograph method, as described in Non-Patent Document 2, the time change in the force acting on a sample is measured when the sample is immersed in a liquid. The force (equilibrium wetting load) is measured when the force acting on the sample becomes relatively constant, and this method is effective in evaluating, for example, solderability.

[0004] Patent Document 1 proposes a method for more simply evaluating the wettability of a solid to a liquid. Specifically, two solids to be evaluated are placed opposite each other to create a V-shaped body, which is then immersed in the evaluation liquid, and the value of the rise height from the liquid surface to the wall surface is measured, and the measured value is used to evaluate the wettability of the solid to be evaluated to the liquid. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] "Surface Tension" by Shu Ono, Kyoritsu Shuppan, 1980, p.82 [Non-Patent Document 2] Sadayuki Fujima, "Evaluation of Solder Wettability of Films Using Meniscograph," Surface Technology, Vol. 63, No. 11, 2012, p. 660 [Non-Patent Document 3] YUNKYUM KIM “Wettability of MnxSiyOz by Liquid Zn-Al Alloys”, METALURGICAL MATERIALS TRANSACTIONS B, 2010, Vol.14B, p.872 [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 06-148056 Summary of the Invention [Problem to be solved by the invention]

[0007] The methods described in Non-Patent Document 1 include a method of directly measuring the contact angle and a method of photographing the outline of the droplet and measuring the angle by image analysis. However, the former method has a problem with accuracy because it is based on subjective judgment, and the latter method has a problem with the complicated operation. In addition, this method has the disadvantage that the measurement error increases as the contact angle increases. Furthermore, these methods are intended for measurement at room temperature, and there is a problem that it is difficult to measure at high temperatures and on molten materials that are easily oxidized.

[0008] In contrast, in Non-Patent Document 3, the stage for conducting the droplet test is placed in a chamber capable of high-temperature reduction annealing, and the wettability of high-temperature molten zinc on any steel sheet is evaluated. However, this type of evaluation method only evaluates the wettability of a minute amount of liquid on the steel sheet, which is problematic in that it is significantly different from an actual process in which steel sheets are continuously immersed in liquid, such as in a hot-dip galvanizing line.

[0009] The meniscograph method described in Non-Patent Document 2 is a method in which a sample is immersed in a liquid, and it is possible to evaluate wettability similar to that in an actual process. In this method, when the sample is immersed in a liquid, it is necessary to measure minute changes in the force acting on the sample over time, and in addition to requiring high accuracy as with the above-mentioned method, high-precision load measurement equipment is essential for the measurement, and it also requires skill.

[0010] In response to this, Patent Document 1 proposes a method for more simply evaluating the wettability of a solid to a liquid. Specifically, two evaluation target solids are placed facing each other to create a V-shaped body, which is then immersed in the evaluation liquid, and the value of the rise height from the liquid surface to the wall surface is measured, and the measured value is evaluated as the wettability of the evaluation target solid to the liquid. However, in the numerical comparison described in Patent Document 1, only the evaluation target must be changed under the same conditions. Specifically, only the conditions to be targeted are changed from the evaluation liquid, liquid temperature, test piece size, immersion speed, immersion depth, etc., and a relative comparison is performed. Therefore, there is a problem that it is difficult to measure absolute parameters such as the wetting contact angle. Furthermore, due to the constraints of the evaluation method, it was difficult to measure the wettability of a high-temperature molten material such as hot-dip metal plating.

[0011] An object of the present invention is to propose a method for evaluating the wettability of a solid surface with a liquid quantitatively with high accuracy without requiring load measurement equipment.

[0012] Furthermore, an object of the present invention is to propose a method for evaluating the wettability of a solid surface, which makes it possible to set the conditions of the environmental atmosphere to which the solid surface above the evaluation liquid surface is exposed. [Means for solving the problem]

[0013] The inventors of the present invention have conducted extensive research to solve the above problems, and have found that a pair of solids having test surfaces facing each other at a certain distance from each other can be immersed horizontally in a test liquid, and the difference between the liquid level at which the liquid penetrates into the gap between the pair of solids and the test liquid level, i.e., the wetting height, can be measured, and the surface wettability of the solid can be evaluated by the measured value. This method makes it possible to evaluate the wettability of the solid surface with a liquid with high accuracy without using a load measurement device.

[0014] It is particularly suitable for evaluating with high precision the wettability of a solid surface with respect to molten metal under controlled atmospheric conditions.

[0015] The present invention has been made based on these findings, and has the following gist. [1] Two solids are placed facing each other with their evaluation surfaces separated, and the entire lower ends of the two solids are arranged so that they are on the same plane to form a test material. An immersion test is then performed in which the test material is immersed in the evaluation liquid so that the entire lower end of the test material is parallel to the surface of the evaluation liquid; measuring the difference between the liquid level of the evaluation liquid penetrating into the gap between the two solids for an arbitrary immersion time and the height of the surface of the evaluation liquid, i.e., the wetting height; The measured value is used as an evaluation value of the wettability of the solid surface with the evaluation liquid. [2] The method for evaluating the wettability of a solid surface described in [1], wherein a contact angle between the solid and the evaluation liquid is calculated based on the wetting height and the gap width between the solids, and the contact angle is used as an evaluation value for the wettability of the solid surface with the evaluation liquid. [3] Gap width between solids after the immersion test w 試験後 Measure the gap width w 試験後 and the gap width w between the solids before the immersion test 試験前 Based on this, the wet height h is corrected by the following formula (1), and the corrected wet height h 補正後 The method for evaluating the wettability of a solid surface according to [1] or [2], wherein the wettability of the solid surface with the evaluation liquid is evaluated by: h 補正後 =(h w試験後 ) / w 試験前 (1) [4] Wet height h after correction 補正後 , and the gap width w between the solids after the immersion test 試験後 and calculating a contact angle between the solid and the evaluation liquid from the above, and using the contact angle as an evaluation value for the wettability of the solid surface with the evaluation liquid. [5] A method for evaluating the wettability of a solid surface according to any one of [1], [2], [3] or [4], in which the wetting spreading rate of the solid-liquid interface is calculated from the change in the height of the liquid surface penetrating into the voids between the solids when the immersion time in the immersion test is changed. [6] A method for evaluating the wettability of a solid surface according to any one of [1], [2], [3], [4] or [5], wherein the atmosphere above the evaluation liquid surface during or before immersion in the immersion test is controlled. [7] The method for evaluating wettability of a solid surface according to [6], wherein the evaluation liquid is a molten metal. [8] The method for evaluating wettability of a solid surface according to [7], wherein the evaluation liquid is molten zinc. Effect of the Invention

[0016] According to the present invention, the wettability of a solid surface with respect to a liquid can be evaluated with high accuracy without the need for load measurement equipment. In addition, it is also possible to calculate the wetting spreading speed of the solid-liquid interface, and it is possible to set the conditions of the environmental atmosphere to which the liquid surface to be measured is exposed. As a specific application method, the wettability of a solid surface with respect to a high-temperature liquid can be simply and quantitatively measured. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a schematic diagram showing a test material for evaluating surface wettability according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a test material for evaluating surface wettability of the present invention, taken in a direction perpendicular to the evaluation surface when immersed in an evaluation liquid. [Diagram 3] FIG. 3 is a diagram for explaining the meniscograph method described in Non-Patent Document 2. [Figure 4] FIG. 4 is a schematic diagram of the wetting up process when the liquid surface is well wetted. [Diagram 5] FIG. 5 is a top view of a test material for evaluating surface wettability in which the solid expands due to an increase in temperature. [Figure 6] FIG. 6 is a cross-sectional view taken along line AA' in FIG. [Figure 7] FIG. 7 is a top view of a test material for evaluating surface wettability, in which the solid body is dented due to an increase in temperature. [Figure 8] FIG. 8 is a cross-sectional view taken along line AA' in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The method of the present invention is shown in outline in Figures 1 and 2. As shown in Figure 1, first, a test material is prepared by fixing two solids in a pair, that is, a spacer between the two solids so that the surfaces to be evaluated of each solid face each other. The opposed solids and the spacer are fixed as necessary. The surfaces to be evaluated may have a curvature, but from the viewpoint of improving measurement accuracy, it is preferable that they are flat. In addition, a plate-like member having a flat shape is suitable for the solid.

[0019] There is no limitation on the method of fixing the two solids, and welding, screwing, etc. may be used. The spacer may be made of the same material as the solids, or a glass plate or the like may be used to visualize the inside. To evaluate the surface wettability, at least the entire lower ends of the two solids must be arranged so that they are on the same plane. Next, the test material is immersed in the evaluation liquid so that the entire lower end of the test material is parallel to the evaluation liquid surface, the difference between the evaluation liquid level and the immersion liquid height is measured, and the measured value is used as the evaluation value of the wettability.

[0020] The dimensions of the solid are determined by the dimensions of the test material that can be collected and the amount of the evaluation liquid to be immersed, but in order to measure the difference between the evaluation liquid level and the intrusion liquid height, the height of the solid (in the direction perpendicular to the evaluation liquid level) is preferably 10 to 1000 mm. The height of the solid is more preferably 50 mm or more. The height of the solid is more preferably 200 mm or less. The width of the solid (corresponding to the distance between spacers) is preferably 10 to 1000 mm. The width of the solid is more preferably 30 mm or more. The width of the solid is more preferably 150 mm or less.

[0021] The gap width between solids is preferably 2 mm or less in order to clearly distinguish the difference in the height of the penetrating liquid due to differences in wettability. It is more preferably 1.5 mm or less. On the other hand, if the gap width is too narrow, the effect of the shape of the solid becomes large, which may impair accuracy. Therefore, the gap width is preferably 0.2 mm or more.

[0022] Next, the circumstances that led to the discovery of the wettability evaluation method of the present invention will be described. The usefulness of contact angle measurement as a method for evaluating wettability is well known, but as mentioned above, it is not easy to measure the contact angle. Therefore, the inventors focused on the "capillary phenomenon" as a phenomenon that makes it possible to evaluate wettability. The capillary phenomenon is a physical phenomenon in which a liquid inside a thin tubular object rises inside the tube, and the contact angle can be calculated based on the following formula from the liquid level height h inside the tube when this thin tubular object is immersed in the evaluation liquid. h = {2γcosθ / (ρgr)}×10 6 (2) Here, h is the liquid surface height (mm), γ is the surface tension (N / m), θ is the contact angle (°), and ρ is the density of the evaluation liquid (kg / m 3 ), g: Gravitational acceleration (m / s 2 ), r: inner diameter of the capillary (mm).

[0023] However, the above method of deriving the liquid level height is limited to solids that can be made into a tubular shape, and therefore there is a problem that a high-strength steel plate or the like that is difficult to process into a tubular shape cannot be used as a solid for evaluating wettability.

[0024] Therefore, we conducted extensive research to find a simpler and more practical method for evaluating the liquid level, and discovered that a similar "capillary phenomenon" occurs even in test materials with a small gap width, which is the distance between solids, as shown in Figure 1.

[0025] The high strength steel plate described here is, for example, a steel composition containing, in mass %, C: 0.0001% or more and 0.30% or less, Si: 0.001% or more and less than 2.0%, Mn: 0.01% or more and 3.5% or less, P: 0.02% or less, S: 0.01% or less, Al: 0.10% or less, N: 0.006% or less, and further containing Nb: 0.005 to 1%, Ti: 0.005 to 1%, V: 0.005 to 1%, Zr: 0.005 to 1%, Cr: 0.005 to 20%, Ni: 0.005 to 10%, Co: 0.005 to 1%, Mo: 0.005 to 1%, W: 0.005 to 1%, Ca: 0.0001 to 0.01%, Mg: 0.0001 to 0.01%, and ...0.01%, and Nb: 0.005 to 0.01%. . 01%, REM:0.0001~0 . It refers to a steel sheet containing one or more of the following elements as necessary: ​​0.01%, Sn: 0.001-0.2%, Sb: 0.001-0.2%, and B: 0.0001-0.01%, with the balance being Fe and unavoidable impurities. The tensile strength TS of the steel sheet is preferably 270 MPa or more.

[0026] The balance of forces when the test material is immersed is used in the meniscograph method (FIG. 3) described in Non-Patent Document 2, and the following formula holds true. F = γcosθ·l × 10 -3 - Vρg×10 -9 (3) where F is the normal force (N), γ is the surface tension (N / m), θ is the contact angle (°), l is the perimeter of the solid to be evaluated (mm), and V is the volume of the immersed part (mm 3 ), ρ: density of the evaluation liquid (kg / m 3 ), g: Gravitational acceleration (m / s 2 Based on this relational expression, the relationship between the liquid surface height and the contact angle when the test material of the present invention is used will be described.

[0027] A schematic diagram of the wetting up when the liquid surface wetting is good is shown in Figure 4. Here, "wetting up" refers to the phenomenon in which the evaluation liquid wets the surface of the gap between solids and rises up.

[0028] In Figure 4, the intrusion liquid level height from the evaluation liquid level is h (mm) and the gap width is w (mm). In this method in which two solids are placed opposite each other, the intrusion liquid level height h (mm) from the evaluation liquid level represents the difference between the liquid level that intrudes into the gap between the two solids and the surface height of the evaluation liquid. Hereinafter, the intrusion liquid level height h from the evaluation liquid level may be referred to as the wetting height. Here, when the liquid level is stopped, the surface tension of the evaluation liquid due to wettability and the mass of the evaluation liquid in the gap are in balance, so γcosθ·l = Vρg×10 -6 (4) If we assume that the length between the spacers in Figure 1 is L (mm), the above formula can be converted as follows: In this case, the length between the spacers, L, is sufficiently larger than the gap width, w. γcosθ·(2L) = (w·h·L)ρg×10 -6 (5) cosθ = (whρg × 10 -6 ) / (2γ) (6) θ=arccos{(whρg×10 -6 ) / (2γ)} (7) That is, by using this method, the contact angle θ can be derived by measuring the wetting height h at any plate width, and it is found that wettability can be quantitatively evaluated. In addition, by using this method, it is possible to measure the wetting height h between two solids and use the measured value as the evaluation value of the wettability of the solid surface with the evaluation liquid. In addition, according to this method, the wettability of the solid surface with the liquid can be evaluated with high accuracy without using a load measurement device. In addition, in the evaluation of wettability by the method of the present invention, the immersion time of the solid can be set to a specific time, so that the wettability between different samples can be relatively compared and evaluated. In addition, the immersion time at that time may be changed depending on the purpose.

[0029] In addition, the evaluation device used in the wettability evaluation method of the present invention is extremely simple, as shown in FIG. 1. The evaluation device is placed in a sealed device in which the environmental atmosphere can be controlled, and by selecting an equipment material that can be used in the environmental atmosphere, the wettability of a solid surface with respect to a liquid in a high-temperature environment or a corrosive environment can be evaluated with high accuracy.

[0030] In general, it is not easy to make a load measuring equipment usable in a high-temperature environment or a corrosive environment. Here, high temperature means 100°C or higher and 2000°C or lower. In this method, since it is possible to measure wettability even when the evaluation liquid is at a high temperature, it is suitable for evaluating the wettability of a solid surface with respect to molten metal. In particular, when a high-temperature molten material for metal plating is used as the evaluation liquid, which is required from an industrial point of view to evaluate the wettability of a solid surface with respect to the liquid with high accuracy, the temperature of the evaluation liquid is often 100°C or higher and 700°C or lower. The wettability evaluation method of the present invention is particularly suitable for evaluating the wettability of a solid surface with molten zinc, which often has a melting point of 400°C or higher, as the evaluation liquid in metal plating treatment.

[0031] If the two solids are the same, the derived contact angle indicates the wettability of the solid, but if the two solids are different materials, the derived contact angle is the average of the different contact angles of the two solids. Here, the wetting height h is as follows: h = {γ(cosθ 固体1 +cosθ 固体2 ) / (ρgr)}×10 6 (8) Therefore, by using the wettability evaluation method of the present invention, it is also possible to measure the contact angle of the evaluation liquid in a structure in which two solids made of different materials are combined.

[0032] In addition, in the wettability evaluation method of the present invention, the immersion can be performed in a closed device with a controlled atmosphere, so that the wettability of a solid surface to a liquid under various environmental atmospheres can be evaluated with high accuracy. In the case where the high-temperature molten material for metal plating is used as the evaluation liquid, hot-dip galvanizing is assumed. Representative examples of atmospheric elements include hydrogen concentration, oxygen concentration, carbon monoxide concentration, carbon dioxide concentration, and dew point as an index representing water vapor concentration, and it is also possible to evaluate the effect of a gas atmosphere with these elements controlled on wettability.

[0033] Examples of the remaining inert gas in the atmosphere in which the above elements are controlled include nitrogen, argon, and helium. In particular, the present invention has a feature that it is possible to cause a chemical reaction such as an oxidation reaction between the atmospheric gas and a solid in an atmosphere-controlled sealed device, and to cover a part or all of the solid surface with a reaction product produced by the reaction, and to evaluate the wettability of the solid surface to a liquid in that state. For example, a sample made of a steel sheet is held in a gas atmosphere controlled to a predetermined atmosphere for a predetermined time to oxidize the surface of the steel sheet, and the oxide-coated sample is immersed in a high-temperature molten metal for plating without being exposed to the outside air, thereby making it possible to evaluate the wettability of the oxide-coated steel sheet and the plating solution. In other words, the present invention makes it possible to evaluate the wettability of a liquid to be evaluated and a solid coated with a certain coverage rate by a reaction product.

[0034] By carrying out the chemical reaction and wettability evaluation consecutively in the box, it is possible to prevent changes in the crystal structure and adhesion state of the reaction product due to cooling to room temperature, oxidation due to contact with the outside air, etc., and it is advantageous in that wettability can be evaluated with high accuracy. In addition, such evaluation makes it possible to grasp the influence of the gas atmosphere composition on the wettability of the solid with the evaluation liquid. Therefore, in the present invention, it is preferable to control one or more of the temperature, hydrogen concentration, oxygen concentration, carbon monoxide concentration, carbon dioxide concentration, and dew point of the atmosphere above the evaluation liquid surface when or before immersing the solid in the evaluation liquid.

[0035] In addition, this method does not require the test material to be shaped into a cylindrical shape, and is therefore suitable for evaluating the wettability of materials that are difficult to shape, such as high-strength steel plates.

[0036] Furthermore, in general, when a small amount of evaluation liquid is used, the chemical composition of the evaluation liquid may change due to a reaction between the solid surface and the evaluation liquid, or the temperature of the evaluation liquid may change significantly due to the influence of the temperature of the solid. On the other hand, according to the wettability evaluation method of the present invention, the wettability of the solid surface with respect to the evaluation liquid can be evaluated by immersing a sample in the evaluation liquid. That is, by immersing the sample in the evaluation liquid, the changes in the composition of the evaluation liquid and the changes in the temperature of the evaluation liquid can be made negligibly small, and the wettability can be accurately measured even when the changes in the composition and temperature of the evaluation liquid are small.

[0037] For example, when a molten zinc bath is used as the evaluation liquid and a steel sheet is used as the solid, Al in the hot dip galvanizing bath liquid, which is the evaluation liquid, reacts with oxides present in small amounts on the surface of the solid steel sheet to reduce the oxides. Therefore, if a small amount of droplets is used as the evaluation liquid, the consumption of Al in the droplets increases, and Al in the droplets disappears, which may result in insufficient reduction of oxides on the steel sheet surface. Furthermore, if the temperature of the droplets differs from the temperature of the steel sheet after a small amount of droplets is dropped, the smaller the volume of the droplets, the greater the temperature change after the droplets are dropped. As a result, the results are different in terms of chemical composition and temperature from the case in which the evaluation liquid is immersed in the liquid of the present invention. On the other hand, according to the wettability evaluation method of the present invention, since the sample is immersed in the evaluation liquid, the changes in the composition of the evaluation liquid and the changes in the temperature of the evaluation liquid can be made negligible, and the wettability of the solid surface to the evaluation liquid can be accurately evaluated in a state in which the changes in the composition and temperature of the evaluation liquid are small.

[0038] In the wettability evaluation method of the present invention, it is preferable to appropriately set the liquid volume of the evaluation liquid in accordance with the production method assumed for evaluating wettability.

[0039] In order to reduce the effects of changes in the liquid composition and temperature, the evaluation area of ​​the solid is set to 1 mm on one side. 2Per (2mm on both sides 2 The liquid volume of the evaluation liquid was 0.8 mm 3 It is preferable that the thickness is 1.2 mm or more. 3 More preferably, it is equal to or more than that.

[0040] In addition, when evaluating wettability in the present invention, the immersion depth of the solid in the evaluation liquid is preferably 60 mm or less. In the present invention, the wettability is calculated from the difference between the height to which the evaluation liquid has risen to and the bath liquid surface, so the calculation result of wettability is not affected by the immersion depth of the solid. However, by setting the immersion depth of the solid in the evaluation liquid to 60 mm or less, the elements consumed in the reaction between the solid and the evaluation liquid are instantly replenished from the evaluation liquid immersion part at the bottom end of the solid, so that it is possible to suppress changes in the composition of the evaluation liquid that has infiltrated into the gap between the solid. From the viewpoint of suppressing changes in the composition of the evaluation liquid due to the chemical reaction between the solid and the evaluation liquid, the immersion depth of the solid in the evaluation liquid is more preferably 50 mm or less. Furthermore, from the viewpoint of sufficiently replenishing the consumed elements in the evaluation liquid, the volume of the evaluation liquid as a liquid is set to 1 mm2 per one side of the solid area. 2 Per (2mm on both sides 2 per inch), 5mm 3 More preferably, it is equal to or more than that.

[0041] In addition, unlike the conventional method such as that in Patent Document 1, which is based on measurements at room temperature, this evaluation method is particularly useful for evaluation of high-temperature molten metals, etc., where changes in the shape of the solid body due to heating and cooling are a concern. 試験前 and w 試験後 By measuring the height, the wetting height can be corrected based on the following formula, making it possible to evaluate the wettability with higher accuracy. h 補正後 =(h w 試験後 ) / w 試験前 (1) Here, when the shape of the solid changes, this includes cases where the solid bends or warps, causing the shape to change to an indefinite form. In such cases, the gap width w between the solids after the immersion test is 試験後is defined as the distance between solids at the center between the spacers in the immersed part among the distances between solids after the immersion test. Also, the wet height h after the test is defined as the difference between the liquid level on the center line between the spacers in the immersed part in the direction perpendicular to the liquid level and the surface height of the evaluation liquid. Furthermore, the corrected wet height h 補正後 and the gap width between the solids before the test w 試験前 The estimated wetting contact angle θ after correction is calculated by substituting the spacer distance L into equation (7). 補正後 It is also possible to obtain

[0042] Furthermore, according to the method of the present invention, not only is it possible to derive the wetting contact angle for a specific immersion time, but by intentionally changing the immersion time, it is possible to calculate the wetting expansion rate of the solid-liquid interface of multiple test materials with different immersion times, i.e., the change in the wetting contact angle over time, from the change in the height of the liquid surface penetrating into the gap between the two solids of the test material.

[0043] In addition, if the evaluation liquid level rises and falls with the passage of immersion time, it is necessary to measure the evaluation liquid level as well as the liquid level penetrating into the gap.

[0044] There is no specific method for calculating the wetting spreading rate. However, for example, it can be roughly calculated as follows based on the difference in immersion time between 1 s and 5 s, which is when the change in wetting height is greatest. (estimated wetting contact angle θ 1s 補正後 - Estimated wet contact angle θ 5s 補正後 ) / 4s Here, the estimated wetting contact angle θ 1s 補正後 " refers to the estimated wetting contact angle after correction at an immersion time of 1 s, but the estimated wetting contact angle after correction is the actual measured wetting height. h、 Gap width between solids before and after immersion test w 試験前 , and w 試験後 The corrected wet height h calculated by substituting into equation (1) 補正後 The angle is estimated by equation (7) using EXAMPLES

[0045] Molten zinc containing 0.2 mass% Al at 460°C was used as the evaluation liquid, and pure iron plate was used as the solid. In addition, a solid in which SiO2 or MnO was formed on a pure iron plate by PVD to an average thickness of 1 μm was also used. SUS304 plate was used as the spacer. Two solids of the same shape were used as the test material, and holes were drilled to penetrate the solid and the spacer, and then fixed with bolts and screws. The test material shown in Figure 1 was created using this solid, and first recrystallization annealed at 700°C, then cooled to 460°C, and the entire evaluation device was placed in a sealed device in which the atmosphere above the molten zinc bath was controlled to 10% H2-balance N2 and unavoidable impurities, preventing oxidation of the molten zinc bath and the solid. In this state, the test material was immersed in the molten zinc bath for 1 to 60 seconds. After immersion, the spacer part of the test material was cut with a microcutter, and the height to which the molten zinc had risen was visually measured, and the difference from the bath surface was calculated to be the wet height. Here, the measurement of the wetting height was carried out on the center line of the immersed part of the solid farthest from the spacer in the direction perpendicular to the liquid surface.

[0046] The wetting height corresponds to the difference h between the liquid level entering the gap and the surface height of the evaluation liquid in Figure 4. In this case, when the wetting height was lower than the bath surface, the wetting height was calculated as a negative value.

[0047] The gap width between the two solid pieces of the test material was set to 0.2 mm to 1.2 mm, and the gap width after the immersion test was also measured for the gap width between the solid pieces at the center between the spacers. As shown in Figure 5, when the shape of the solid changes with heating and cooling, the wet height was corrected using equation (1). The results are shown in Table 1.

[0048] [Table 1]

[0049] In Table 1, the immersion time of 1 second corresponds to the evaluation result of the initial wetting. The estimated wetting contact angle corresponds to the result calculated from the gap width and the wetting height. At this time, the surface tension of molten zinc at 460°C, γ: 0.77 N / m, zinc density ρ: 6.570 g / cm 3 , gravitational acceleration g:9.8m / sec 2 was used.

[0050] Looking at the initial wettability of each solid, it can be seen that pure iron has very good wettability, but the solids on which SiO2 and MnO are formed have poor wettability and the estimated contact angle is large. Regarding the wettability of molten zinc on such oxides, for example, Non-Patent Document 3 reports that the static wet contact angle of molten zinc on SiO2 and MnO is approximately 120°. However, by measuring the contact angle using the method used in this study, it became clear that the contact angle assuming an actual process would be even larger than the contact angle reported in Non-Patent Document 3.

[0051] Furthermore, when the immersion time was 5 seconds or more, the wetting height increased for the pure iron and the solid with the MnO film formed. This is because in a system in which an alloy reaction occurs, such as between molten zinc and pure iron, the iron-zinc alloy reaction progresses over time, causing an increase in the wetting height (wetting expansion). Therefore, the contact angle calculated from this wetting height corresponds to a value where initial wetting and wetting expansion are mixed, and is listed only as a reference value.

[0052] On the other hand, the wet height of the solid with the SiO2 coating hardly changed with the immersion time, suggesting that the iron-zinc alloy reaction rate on the solid with the SiO2 coating is much slower than that on the other two solids.

[0053] There are no specific regulations for the method of estimating the wetting spreading rate, but here we made the following estimate based on the difference in immersion time from 1 s to 5 s, which is when the change in wetting height is greatest. Wetting spread rate = (Estimated wetting contact angle θ 1s 補正後 - Estimated wetting contact angle θ 5s 補正後 ) / 4s (9) As described above, by using the present invention, the wettability of a solid surface to any liquid can be obtained more simply and as a numerical value, and the wettability spreading behavior can also be quantitatively compared and evaluated. Even if the shape of the solid changes with heating and cooling, the wettability of the solid surface can be obtained more simply and as a numerical value by correcting the surface height of the evaluation liquid based on the change in the gap width between the solids. In addition, the wettability of a solid surface to a liquid under a specific environmental atmosphere can also be measured. In particular, the present invention makes it possible to evaluate the wettability of a solid surface to a plating bath liquid under conditions that assume the actual operation of hot-dip galvanizing, which is widely used in industry. [Explanation of symbols]

[0054] 1 solid 2 Spacers 3 Gap width 4. Evaluation solution 5 Infiltrated liquid level 6. Evaluation liquid level F is the normal force, γ surface tension l perimeter of the solid V is the volume of the immersed part θ contact angle h Intrusion height from the evaluation liquid level w void width h 補正後 Corrected wetting height w 試験前 Gap width before immersion test w 試験後 Gap width after immersion test

Claims

1. Two solids are placed opposite each other with their evaluation surfaces separated, and the entire lower ends of the two solids are arranged on the same plane to prepare a test material. An immersion test is then performed in which the test material is immersed in the evaluation liquid so that the entire lower end of the test material is parallel to the surface of the evaluation liquid; measuring a difference between the liquid level of the evaluation liquid penetrating into the gap between the two solids for an arbitrary immersion time and the height of the surface of the evaluation liquid, i.e., a wetting height h; When a contact angle between the solid and the evaluation liquid calculated based on the wetting height h or the wetting height h and a gap width between the solids is set as an evaluation value of wettability of the solid surface with the evaluation liquid, a gap width w after test between the solids after the immersion test is measured, and the wetting height h is corrected by the following formula (1) based on the gap width w after test and the gap width w before test between the solids before the immersion test, and the corrected wetting height h after correcting, or a corrected estimated wetting contact angle θ after correcting between the solid and the evaluation liquid calculated from the corrected wetting height h after correcting and the gap width w after the immersion test, is set as an evaluation value of the wettability of the solid surface with the evaluation liquid. h after correction = (h w after test) / w before test (1)

2. The corrected wet height h 補正後 , and the corrected estimated wetting contact angle θ 補正後 2. The method for evaluating wettability of a solid surface according to claim 1, wherein the wettability of the solid surface with the evaluation liquid is evaluated by:

3. 3. The method for evaluating wettability of a solid surface according to claim 1, further comprising the step of calculating a wetting spreading rate of a solid-liquid interface from a change in the evaluation value obtained by changing a height of a liquid surface penetrating into the voids between the solids when an immersion time in the immersion test is changed.

4. 3. The method for evaluating wettability of a solid surface according to claim 1, wherein an atmosphere above the evaluation liquid surface during or before immersion in the immersion test is controlled.

5. The method for evaluating wettability of a solid surface according to claim 3 , further comprising controlling an atmosphere above the evaluation liquid surface during or before immersion in the immersion test.

6. 3. The method for evaluating wettability of a solid surface according to claim 1, wherein the evaluation liquid is molten zinc.

7. The method for evaluating wettability of a solid surface according to claim 3 , wherein the evaluation liquid is molten zinc.

8. The method for evaluating wettability of a solid surface according to claim 4 , wherein the evaluation liquid is molten zinc.

9. The method for evaluating wettability of a solid surface according to claim 5 , wherein the evaluation liquid is molten zinc.

Citation Information

Patent Citations

  • Capillary inner surface static contact angle calculation and test method and test system

    CN112710588A

  • Method for testing electrolyte wettability of electrode plate of lithium ion secondary battery

    CN113188957A

  • Testing method of soldering

    JP1978137054A

  • JP1990150550U

  • Method for evaluating surface wetting property of solid against liquid

    JP1994148056A